Analisa Jatuh Tegangan Dan Penanganan Pada Jaringan Distribusi 20 kV Rayon Palur Pt. PLN (Persero) Menggunakan Etap 12.6 - Kurniawan, Arif, Umar, S.T., M.T (2017)
PLN (Persero) is a state-owned company engaged in electricity and maintenance service provider of electricity to consumers. At the time of distribution of electric energy will likely disruption that appears, one of which is the voltage drop. In this study, researchers will conduct Analisia the voltage drop on the feeder 07 Palur 20 KV distribution network PT. PLN UPJ Palur, before the analysis is done, the researcher will seek information and data necessary. Data taken from the PT. PLN UPJ on the feeder 07 Palur interview method. When creating a network diagram feeder line 07 Palur using 12.6 ETAP program course with the analysis of the results that can be known the size of the voltage drop. From haasil when there is interference voltage drop analysis using ETAP simulation 12.6 with most large voltage drop is 19.857 KV with a voltage drop of 1,581 KV and a percentage drop 0,00611 %. A large voltage drop pda channel is still within the standard tolerance PLN ie -10% of its nominal voltage. The voltage drop is influenced by the length of the conductor and the value impedance where the value is influenced by the value of the channel resistance and reactance values, the greater the value of reactance and resistance value, the voltage drop will be even greater.